The Values of Local Wisdom of Minangkabau Culture in a Baralek Gadang Traditional Wedding - Helzi Ramanta; Samsuri Samsuri (Bina Nusantara University, 2020)
The research aimed to (1) describe the traditional Minangkabau Baralek Gadang marriage; (2) analyze the procedures for the Minangkabau traditional wedding ceremony Baralek Gadang; (3) analyze the values of local wisdom in the traditional Minangkabau wedding Baralek Gadang. The research method applied was qualitative research, which was a literature study. Sources of data were books, journals, and internet sites related to the selected topic. The research data source consisted of books and journals about local wisdom of the Minangkabau culture in the customary marriage of Baralek Gadang. Data collection was carried out using documentation techniques, looking for data about things or variables in the form of notes, books, papers or articles, and journals. The data analysis technique used in the research was the content analysis method. The results show that (1) customary marriage in the Minangkabau community is identical with the existence of traditional ceremonies, which have many unique things and some rules that must be obeyed both based on customary provisions and Islamic teachings. The traditional wedding procession in Minangkabau custom has several conditions that must be carried out before getting married. (2) The procedures for the traditional Minangkabau Baralek Gadang wedding ceremony include the preparation for the wedding, the implementation of the wedding, and the implementation after the wedding ceremony. (3) The values of local wisdom contained in Minangkabau Baralek Gadang customary marriages include religious values, social values, knowledge values, language values, and artistic values.